THERAPEUTIC PROTEINS AND PEPTIDES FROM EDIBLE AND MEDICINAL MUSHROOMS-REVIEW - J. Lavanya; S. Subhashini (European Scientific Journal, ESJ, 2013)
Bioactive proteins and peptides were reported from many sources ranging from bacteria to humans. Many of them are having various bioactive characteristics like antibacterial, antifungal, antiparasitic, antihypertensive, antisporadical, anticancer etc., Moreover; many antimicrobial peptides employ sophisticated and dynamic mechanisms of action to effect rapid and potent activities consistent with their likely roles in antimicrobial host defense. The molecules exhibit an antimicrobial activity against bacteria, viruses, and eukaryotic pathogens with different specificities and potencies depending on the structure and amino-acid composition of the proteins and peptides. Here we summarize investigations on bioactive proteins and peptides from edible and medicinal mushroom and discuss prospects for therapeutic applications.